2010
DOI: 10.1186/cc8911
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of serum leptin monitoring and its correlation with tumor necrosis factor-α in critically ill patients: a prospective observational study

Abstract: IntroductionSevere infection and sepsis are common causes of morbidity and mortality. Early diagnosis in critically ill patients is important to reduce these complications. The present study was conducted to determine the role of serum leptin at early diagnosis and differentiation between patients with manifestations of systemic inflammatory response syndrome (SIRS) and those with sepsis in patients suffering from a broad range of diseases in the intensive care unit (ICU) and its correlation with other biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 22 publications
6
42
0
7
Order By: Relevance
“…37 In 2010, Yousef et al published a prospective observational study which confirmed a positive correlation between leptin and IL-6 and TNF-ɑ in patients with sepsis. 39 The same study concluded that elevated leptin levels can distinguish between sepsis and non-infectious systemic inflammatory response syndrome with a sensitivity of 91.2% and a specificity of 85% for a threshold of 38 µg/L.…”
Section: Leptinmentioning
confidence: 91%
“…37 In 2010, Yousef et al published a prospective observational study which confirmed a positive correlation between leptin and IL-6 and TNF-ɑ in patients with sepsis. 39 The same study concluded that elevated leptin levels can distinguish between sepsis and non-infectious systemic inflammatory response syndrome with a sensitivity of 91.2% and a specificity of 85% for a threshold of 38 µg/L.…”
Section: Leptinmentioning
confidence: 91%
“…In animal and human studies administration of endotoxin and TNF-α as inducers of severe systemic inflammation resulted in significant elevation of serum leptin levels [63]. Yousef and colleagues also reported increased values for IL-6, CRP, TNF-α and leptin at admission to ICU, with leptin threshold values of 38 µg/l for distinguishing between SIRS and sepsis [7]. Controversially, among other studies, a study from Denmark revealed low leptin levelsand also low adiponectin and RBP4 levels -at admission to the ICU, possibly due to an acute stress response [64].…”
Section: Leptin and Leptin-receptormentioning
confidence: 99%
“…Early differentiation between sepsis and SIRS is a considerable problem in the treatment of patients on ICU. Due to the early systemic release of inflammatory cytokines as compared with synthesis of acutephase-proteins, cytokines have been widely investigated for their diagnostic potential in predicting sepsis [7]. Nevertheless, until now the perfect biomarker for differentiation of sepsis and SIRS has not been found yet and ongoing research focuses on identification of appropriate diagnostic biomarkers for sepsis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Human septic patients have evidence of increased circulating leptin concentrations which correlate with severity of illness, and hence it has been postulated that leptin may play a critical role in the pathogenesis of sepsis-associated multi-organ dysfunction [90]. It has also been suggested that elevated leptin levels may aid in distinguishing between sepsis and non-infectious SIRS [91]. However, research in this area is in its infancy, and further studies are required to determine the pathogenic mechanisms of leptin, and the diagnostic and therapeutic potential of leptin family molecules in human sepsis.…”
Section: Leptinmentioning
confidence: 99%